Efektivitas Pendekatan Rational Emotive Behavior Therapy melalui Bimbingan Kelompok untuk Mengatasi Stres Akademik Siswa - Konadi, Husrin; Mudjiran, Mudjiran; Karneli, Yeni (Konselor, 2017)
Rational Emotive Behavior Therapy (REBT) Approach is one of the ways to change irrational thinking about academic stress and group guidance is an effective service and tools to support the implementation of the REBT approach in order to overcome the students’ academic stress in SMA Negeri 3 Padang. This research was used The Non Equivalent Control Group which was classified in the Quasi Experimental The Subject of this research was 10 students of the experimental group which identified as having very high, high, medium, low and very low academic stress. Instrument of this research was used academic stress scale that has qualified the instrument research, and then analyzed by used Wilcoxon Signed-Rank Test and Kolmogorov Smirnov 2 Independent Samples.  The findings of this study show in general that REBT Approach through group guidance was Effective to overcome the students academic stress. In Specific (1) there was a significant difference in scored on the student's academic stress of the experimental group(2) there was significant difference in scored on students’ academic stress in the control group (3) There were significant differences in scored on students’ academic stress in the experimental group which following the REBT approach through group guidance with Control group, which following the REBT Approach without REBT Appoach.